Zombie Semiotics and the Economics of the Apocalypse - Hartley, John (Recherches sémiotiques / Semiotic Inquiry, 2021)
This paper explores the relations between economics and semiotics, using as its main conceptual lever the figure of the zombie. John Quiggin, Paul Krugman and others criticise the persistence of ‘undead ideas’ in economics. The paper applies this perspective to urban semiosis, where undead monuments have become key sites for staged conflict across the world. Working from Doru Pop’s critique of ‘zombie semiotics’, the paper turns from fiction to the realities of the digital semiosphere and technosphere. Using Juri Lotman’s model, it shows how the climate and coronavirus crises are globally mediated but not self-regulated. It identifies reflexive autocommunication as the means for semiospheric response to planetary crises. Zombie economics and conflict media spread fear of automation and ‘useless’ populations, while techno-entrepreneurs plan to abandon the planet to the apocalypse. It is left to autocommunication among teenage activists to contest the real zombies.